Pengaruh Debt To Asset Ratio, Inventory dan Earning Per Share terhadap Harga Saham pada Industri Subsektor Farmasi yang Terdaftar di BEI - Umar Hamdan Nst; Syamsurizal Syamsurizal; Cut Zahri (Universitas Batanghari Jambi, 2021)
This research understands the impact of Debt to Assets Ratio, Inventory Turnover and Earning Per Share on Share Prices in pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The research population used was 9 issuers and a total sample size of 45 samples. Statistical research methods use quantitative. The assumption data analysis method is the classical assumption test. Hypothesis test with regression test, t-test, and f-test. Based on the results of the partial test (t), DAR and ITO have no effect on stock prices but EPS has an effect on stock prices. Meanwhile, the simultaneous test results (f) of DAR, ITO and EPS have no impact on stock prices. The result of the Adjusted R Square (R2) hypothesis test is 21%, it can be said that the Debt to Assets Ratio (X1), Inventory Turnover (X2) and Earning Per Share (X3) variables have an effect on stock prices by 21% and the rest is 79%. audits by other variables not included in this research